Analysis of Stroke Rate and Stroke Length in Relation to Freestyle Swimming Speed Among Indonesian Student Athletes - Prijoto, Prijoto; Kurniati, Rizki; Sumintarsih, Sumintarsih; Yulianto, Wahyu Wibowo Eko; Nugraheningsih, Ginanjar (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
In competitive swimming, small performance margins make technical regulation a key determinant of race outcomes. Stroke rate (SR) and stroke length (SL) are critical kinematic variables that interact to determine freestyle swimming speed, yet their distance-specific regulation in developing swimmers remains unclear. This study aimed to identify SR-SL profiles across race distances and examine their relative contributions to freestyle speed in Indonesian student-athletes. A cross-sectional observational design was applied to 80 finalist performances across 10 freestyle events. Kinematic data were obtained using mid-pool video analysis, and partial regression analysis assessed the relative effects of SR and SL on swimming speed. The results revealed a clear distance-related shift in stroke regulation. In men, SR decreased from 1.00 to 0.59 cycle·s⁻¹, while SL increased from 1.93 to 2.44 m·cycle⁻¹. In women, SR decreased from 0.96 to 0.63 cycle·s⁻¹, whereas SL increased from 1.78 to 2.19 m·cycle⁻¹. Regression analysis showed that SL was the dominant predictor of speed in most events, particularly in middle- and long-distance races, whereas SR had a stronger influence mainly in sprint events, especially the women’s 50 m. These findings indicate a distance-specific shift from frequency-oriented strategies in sprint events to efficiency-oriented strategies in longer races. Compared with elite swimmers, Indonesian student-athletes rely more on higher SR and shorter SL, likely reflecting developmental and technical constraints. This study highlights that SR-SL regulation is both distance- and development-dependent, with implications for age-appropriate and distance-specific training.